Rasburicase-induced haemolysis and methemoglobinemia: an ongoing issue. Issue 3 (16th March 2021) - Madanat, Luai; Schoenherr, Daniel; Wey, Elizabeth; Gupta, Ruby
Abstract : We report a case of a 91-year-old Caucasian woman with a history of chronic lymphocytic leukaemia who developed acute hypoxic respiratory failure (AHRF) requiring intubation for less than 24 hours after receiving rasburicase. Laboratory workup was significant for methemoglobinemia and acute anaemia, and blood film demonstrated evidence of oxidative haemolysis with bite cells. The patient was given a presumptive diagnosis of glucose-6-phosphate dehydrogenase (G6PD) deficiency and was managed conservatively with successful resolution of AHRF and stabilisation of haemoglobin level. Seven days after admission, she passed away due to subsequent complications; hence, follow-up G6PD level could not be obtained. Haemolytic anaemia and methemoglobinemia in the setting of recent rasburicase administration should raise clinical suspicion for G6PD deficiency. In non-emergent cases, patients should be screened prior to receiving rasburicase regardless of risk factors. Because rasburicase is often needed emergently, patients at high risk of tumour lysis syndrome should be screened early for G6PD deficiency.